"Smart" carboxymethylchitosan hydrogels crosslinked with poly(N-isopropylacrylamide) and poly(acrylic acid) for controlled drug release. (April 2015) - Jankaew, Rathanon; Rodkate, Nantharak; Lamlertthon, Supaporn; Rutnakornpituk, Boonjira; Wichai, Uthai; Ross, Gareth; Rutnakornpituk, Metha
Abstract: Carboxymethylchitosan (CMC) hydrogels containing thermo-responsive poly( N -isopropylacrylamide) (poly(NIPAAm)) and pH-responsive poly(acrylic acid) (poly(AA)) were prepared via a free radical polymerization in the presence of hexamethylene-1, 6-di-(aminocarboxysulfonate) crosslinking agents. A proper ratio of CMC to NIPAAm and AA used in the reaction was investigated such that the thermo- and pH-responsive properties of the hydrogels were obtained. Water swelling of the hydrogels was improved when the solution pH was in basic conditions (pH 10) or the temperature was below its lower critical solution temperature (LCST). Effects of the change in solution temperature and pH on water swelling properties of the hydrogel as well as the releasing rate of an entrapped drug were also investigated. The hydrogels were not toxic and showed antibacterial activity against Straphylococcus aureus ( S. aureus ). The pH- and thermo-responsive properties of this novel "smart" hydrogel might be efficiently used as dual triggering mechanisms in controlled drug release applications.